Determination of leachate compounds relevant for landfill aftercare using FT-IR spectroscopy. (September 2016) - Lenz, Sabine; Böhm, Katharina; Ottner, Reinhold; Huber-Humer, Marion
Highlights: FT-IR spectroscopy can be used to monitor leachate from operating and abandoned landfills. Determination of NH4 -N, NO3 -N, SO4 -S and DOC of leachate by FT-IR spectroscopy. FT-IR prediction models are time-saving and less error prone. Get an insight on processes in the waste-body by landfill leachate investigations. Reactivity of organic matter in waste material is reflected by landfill leachate. Abstract: Controlling and monitoring of emissions from municipal solid waste (MSW) landfills is important to reduce environmental damage and health risks. Therefore, simple and meaningful monitoring tools are required. This paper presents how Fourier Transform Infrared (FT-IR) Spectroscopy can be used to monitor leachate from various landfill sites. The composition of percolated leachate provides information about reactivity or stability of organic matter in landfills. Chemical compounds of investigated leachate are depicted by distinct spectral pattern. Partial least squares regression (PLS-R) models, a multivariate analysis tool, were developed based on infrared spectra to determine simultaneously conventional parameters such as ammonium, nitrate, sulfate, and dissolved organic carbon. The developed models are appropriate for application in waste management practice with respect to their excellent coefficients of determination, namely R 2  = 0.99, 0.99, 0.98, and 0.98, their low errors of cross-validation and their high ratios of performance to deviation (RPD = 9.3, 12.5, 6.5, 7.3). Thus, FT-IR spectroscopy turned out to be a reliable, time-saving tool to determine four parameters relevant for landfill aftercare monitoring by one single easy adaptable measurement.